L’accompagnement à l’orientation par les professeurs principaux de Terminale - Paul Lehner; Clément Pin (Éducation et Socialisation)
This article uses the concept of mandate to examine the social conditions and the effectiveness of the expansion of the role of principal teachers in guidance. After resituating the mandate in its historical-political configuration, the article examines the frequency and nature of the support provided to students and the degree of commitment of teachers. From these two axes, the article sketches a typology of four figures of accompaniment.